Magnetic graphene molecularly imprinted polypyrrole polymer (MGO@MIPy) for electrochemical sensing of malondialdehyde in serum samples - Montoro-Leal, Pablo; Zougagh, Mohammed; Sánchez-Ruiz, Antonio; Rios, Angel; Vereda-Alonso, Elisa Isabel (Elsevier, 2022)
A modified screen-printed carbon electrode (SPCE) has been designed and fabricated for the determination of malondialdehyde (MDA), an important biomarker of oxidative stress. Magnetic graphene oxide (MGO) was synthesized and coated by a molecularly imprinted polypyrrole (MIPy) for the preparation of a novel hybrid nanomaterial (MGO@MIPy). The nanocomposite has been characterized using different spectroscopic and imaging techniques. The coupling of MIPy with MGO allows the exploitation of the magnetic properties of the material for separation, preconcentration and manipulation of analyte which is selectively captured onto the MIPy surface of the nanocomposite. Besides, the derivatization of MDA with diaminonaphtalene (DAN) was carried out, resulting in a more electroactive molecule (MDA-DAN). MDA-DAN was used as template in the synthesis of MIPy. SPCEs were employed to monitor the differential pulse voltammetry (DVP) levels of the material, which is related to the amount of the captured analyte. Under optimum conditions, the nanocomposite-based sensing system has proved to be suitable for the monitoring of MDA, presenting a wide linear range (0.01–100 µM), high sensitivity (experimental LOQ = 0.01 µM) and precision (RSD = 4%). For validation purposes, three chicken serum samples were analysed by external calibration, obtaining recoveries values close to 100% for all the spiked tests. Finally, the developed electrochemical sensor demonstrated to be adequate for bioanalytical application, presenting an excellent analytical performance for the routine monitoring of MDA in serum samples.
Keywords: Grafeno; Magnetismo; Malondialdehyde; Derivatization; Molecularly imprinted polypyrrole; Magnetic graphene oxide; Serum samples